Fostering Employability through Versatility within Specialisation in Medical Translation Education - Muñoz-Miquel, Ana; Montalt, Vicent; García-Izquierdo, Isabel (HERMES - Journal of Language and Communication in Business, 2020)
The current increase of automation (Rodríguez 2017; Massey/Wieder 2018) and the emergence of new needs and forms of communication are triggering substantial changes in the translation profession, in the role of the translator and in translator education. Previous studies (Muñoz-Miquel 2014, 2016a, 2018) have shown the rich variety of tasks — beyond those traditionally considered — that medical translators perform in the workplace, including heterofunctional translation, editing, or community management. The ability to develop new skills and to adapt continuously to the changing needs of the market is one of the essential characteristics of the translator in the 21st century. That is why we consider it of critical importance that, together with specialisation, versatility is promoted in translator education. In this article, we explore the notion of versatility and propose a teaching strategy that incorporates it and can contribute to improving the employability of future translators. Specifically, we put forward some pedagogical proposals for the English-Spanish language combination that promote diversification of competences and tasks within a narrow specialisation — the medical and healthcare field — in order to provide (future) translators with the versatility necessary to respond to new demands and thus be more employable. Our approach is based on the results of surveys of professional medical translators on the tasks and roles they perform, as well as on our own teaching experience in a master’s degree programme in medical translation.